Determinant of Islamic Stock Index in Indonesia Pre and Post Pandemic Era Vaccine - Riyan Andni; Muhammad Said (Journal of Islamic Economics Lariba, 2022)
This study aims to analyze the effect of Inflation, Bank Indonesia (BI) Rate, Exchange Rate, Composite Stock Price Index (JCI), Bank Indonesia Syariah Certificate (SBIS). the World Gold Price both simultaneously and partially against the Indonesian Sharia Stock Index (ISSI). This research applies the methodquantitative approach. The source of research data uses secondary data in December 2019 – December 2021 in the form of monthly closing prices for the Indonesian Sharia Stock Index and the Composite Stock Price Index from https://www.idx.co.id/then closing price Inflation, BI rate, Exchange Rate, Bank Indonesia Syariah Certificate (SBIS) from https://www.bi.go.id/and the closing price of world gold from https://id.investing.com/which was processed using Eviews 12 software with multiple linear analysis. The results of the study show that partially the BI Rate, Exchange Rate, JCI variables have a significant influence on ISSI and the Inflation, SBIS, Price variablesWorld gold has no significant influence on ISSI. Meanwhile, the variables of Inflation, BI Rate, Exchange Rate, JCI, SBIS and World Gold Prices have an effect on ISSI simultaneously. This finding provides implications for policy makers related to the Islamic capital market Keywords: Islamic Stock Index, Inflation, BI rate & exchange rate